Simulation Based Control System for a Manufacturing System - Abdul Rahman, Azrul Azwan; Kernbaum, Sebastian (2007)
The planning of small batches as well as a high level of product variety manufacturing systems and facilities is more complex when involves automation. Therefore solutions for flexible and fast reacting planning methods are needed. The fast evaluation of a high amount of planned manufacturing systems becomes important. A software-based solution could increase the quality and the efficiency of planning processes. Simulation has gained importance in the evaluation of such systems and will be used to support the evaluation processes. In context of this project, robotic and workplace simulation is utilized in planning, evaluation and realization of the flexible manufacturing system. The simulation model is used in order to create, generate and evaluate a control logic program of the system. The simulation model of manufacturing system is developed by utilizing Tecnomatix eM-Engineer. With the help of Siemens product package STEP 7 Professional, the control logic program of the model is tested in virtual commissioning. After iterative improvement steps, the improved control logic program is implemented in the real system.